Analisis Rencana Pengadaan Brake Pesawat Boeing 737 – 300 Menggunakan Metode Economic Order Quantity - Randi Friandana; Freddy Franciscus; Aswan Tajuddin (Jurnal Teknologi Kedirgantaraan, 2024)
PT X is an airline company that serves many flights in Eastern Indonesia. In order to expedite the flight schedule and maintenance system, PT X must have an adequate supply of spare parts, one of the most important spare parts in the aircraft maintenance process is the aircraft brakes. This research aims to determine the control of brake spare part inventory at PT X will be compared with brake spare part inventory control if using Economic Order Quantity. From the results of calculations that have been carried out between the method applied by the company and the EOQ method, it can be seen that using the EOQ method results are more efficient. From the research results it is known that the procurement of brake spare parts if using the Economic Order Quantity (EOQ) method is optimal, with a total inventory cost of Rp. 605,336,000, while the total inventory cost incurred by the company according to company policy is Rp. 783,995,000. So the efficiency of savings obtained by the company if using the EOQ method is Rp. 178,695,000 with an ordering frequency of 6 (six) times and each order is by ordering 13 brakes With this EOQ method, you can increase spending efficiency, avoid delays in providing brake spare parts and also avoid running out of stock of brake spare parts, because the supply of spare parts can be guaranteed to be constant and in accordance with lead time